A 200‐fold Quantum Yield Boost in the Photoluminescence of Silver‐Doped AgxAu25−x Nanoclusters: The 13 th Silver Atom Matters1. Issue 9 (28th January 2014) - Wang, Shuxin; Meng, Xiangming; Das, Anindita; Li, Tao; Song, Yongbo; Cao, Tiantian; Zhu, Xiuyi; Zhu, Manzhou; Jin, Rongchao
Abstract The rod‐shaped Au25 nanocluster possesses a low photoluminescence quantum yield (QY=0.1 %) and hence is not of practical use in bioimaging and related applications. Herein, we show that substituting silver atoms for gold in the 25‐atom matrix can drastically enhance the photoluminescence. The obtained AgxAu25−x (x=1–13) nanoclusters exhibit high quantum yield (QY=40.1 %), which is in striking contrast with the normally weakly luminescent AgxAu25−x species (x=1–12, QY=0.21 %). X‐ray crystallography further determines the substitution sites of Ag atoms in the AgxAu25−x cluster through partial occupancy analysis, which provides further insight into the mechanism of photoluminescence enhancement.